YESTERDAY, TODAY AND FUTURE OF ICT IN SCHOOL - WALAT, Wojciech (Trends in education, 2014)
Modern civilization is based on information and communication technology (ICT) that are basic and essential tools for acquiring, processing, resulting in the creation of knowledge. It is assumed that the next technological revolution will open the school on human intellectual achievements of unprecedented scope and extent. But this requires a change in the school, so as to acquire a large amount of knowledge is based on experience in the application of rules and procedures for the acquisition and processing of information, the vast intellectual sensitivity, because learning is a way of entering into the culture.
Keywords: transformation of education; media in education; ICT; virtual assistant.